A Study on Problems Arises in Practicing Fire Drill in High Rise Building in Kuala Lumpur - Zahari, N.F.; Alimin, A.F.; Sudirman, M.D.; Mydin, M.A.O (EDP Sciences, 2014)
Fire drill is one of the steps taken to mitigate the risk trapped in a building during outbreak of fire. Hence, it is very important for every building to practice fire drill, especially high-rise building. Referring to Fire and Rescue Department of Malaysia (BOMBA), high-rise building had a higher risk compared to other type of buildings. However, there might be problems arise to practice fire drill especially in high-rise building. This research intends to study on fire drill procedure and identify any possible common problems arises when practicing fire drill in high-rise building in Kuala Lumpur. Information was gained through regulations and guidelines associated with fire drill procedure and also parties involved in the practice. Besides, a survey is done for awareness of occupants in high-rise building on fire drill practice. For the case study, three high-rise building are selected in Kuala Lumpur based on specific criteria. Analysis for this research comprises of comparative and descriptive approach as well as statistical analysis which are documented based on case studies and questionnaire survey. The findings indicates that there is no standardized procedure in fire drill, while the most common problems that can be seen in practicing fire drill are lack of commitment among occupants, lack of information on fire drill and output on weaknesses after fire drill been practiced.